Dampak Revolusi Industri 4.0 Terhadap Iman-Moral Remaja dan Pemuda Masa Kini: Pentingnya Pendidikan Agama Kristen - Esti Regina Boiliu; Fredik Melkias Boiliu; Ronald Sianipar (Sekolah Tinggi Teologi Berita Hidup, 2024)
The Industrial Revolution 4.0 era has a significant impact, including on aspects of faith and morals, especially for young people. This article examines these impacts and offers solutions through Christian Education. It is hoped that an understanding of these challenges and solutions can help build a young generation of faith and morality in this digital era. This research uses a qualitative approach with a literature study to analyze the impact of the Industrial Revolution 4.0 on the faith and morals of young people, as well as its implications for Christian Education. This research uses a qualitative approach with a literature study to analyze the impact of the Industrial Revolution 4.0 on the faith and morals of young people, as well as its implications for Christian Education. Christian religious education plays an important role in guiding young people in the era of the Industrial Revolution 4.0. With a proper understanding of the challenges and solutions offered, it is hoped that the younger generation can develop into individuals of faith and morality.Era Revolusi Industri 4.0 membawa dampak signifikan, termasuk pada aspek iman dan moral, khususnya bagi kaum muda. Artikel ini mengkaji dampak tersebut dan menawarkan solusi melalui Pendidikan Agama Kristen. Diharapkan pemahaman tentang tantangan dan solusi ini dapat membantu membangun generasi muda yang beriman dan bermoral di era digital ini. Penelitian ini menggunakan pendekatan kualitatif dengan studi literatur untuk menganalisis dampak Revolusi Industri 4.0 terhadap iman dan moral kaum muda, serta implikasinya bagi Pendidikan Agama Kristen. Penelitian ini menggunakan pendekatan kualitatif dengan studi literatur untuk menganalisis dampak Revolusi Industri 4.0 terhadap iman dan moral kaum muda, serta implikasinya bagi Pendidikan Agama Kristen. Pendidikan Agama Kristen memegang peran penting dalam membimbing kaum muda di era Revolusi Industri 4.0. Dengan pemahaman yang tepat tentang tantangan dan solusi yang ditawarkan, diharapkan generasi muda dapat berkembang menjadi pribadi yang beriman dan bermoral.